Viabilitas dan Vigor Kecambah Aren Pada Berbagai Lama Penyimpanan dan Bahan Pengemasan - Muhammad Salim Saleh; Wardah Wardah; Yusran Yusran (Biology Department, Mathematics and natural science, Tadulako University, 2011)
Research in experimental design was carried out to determine the proper storage period and packing material for maintaining the viability and vigour of sugar palm seedlings. This experiment used Split Plot in Completely Randomized Design. There were two factors were tested. The first factor was storage periods as the main plot, consisted of 7, 14 and 21 days. The second factor was packing materials as subplot, consisted of plastic bag, rice paper and rice paper+plastic bag. Each treatment used three replications. Data was analysed by using Analyses of Variance and differences between treatments were determined by HSD 5% test. Storage periods at 7, 14 and 21 days had an insignificant difference on the viability and vigour of sugar palm seedlings. Packing material from rice paper+plastic bag had a better water content, length of roots, germination rate and dry weight if compared to other packing materials. Packing material from plastic bag is more suitable for 7 days storage, rice paper for 7 and 14 days storage, and rice paper+plastic bag for 7, 14 and 21 days storage on the length of plumula. Key words: Palm, viability, vigour, storage, and packing material.